The Effect of Targhib wa Tarhib Method Implementation on Students' Learning Motivation - Fahriah, Fathia Saidah; Risnawati; Alfiah; Hamdani, M. Fikri (Journal of Islamic Education, 2025)
This study aims to examine the effect of the targhib wa tarhib method on students' learning motivation in Islamic Religious Education at State Senior High School 4 Pekanbaru. This Research employed a quasi-experimental design with a non-equivalent control group design. The Research population consisted of 358 Muslim tenth-grade students at State Senior High School 4 Pekanbaru in the 2023/2024 academic year. The Research sample comprised 60 students selected using a purposive sampling technique, consisting of 30 students in the experimental class (X.7) and 30 in the control class (X.5), based on equivalent academic abilities and class-average scores from first-semester report cards. The treatment was administered across four 90-minute sessions. Data collection techniques employed a learning motivation questionnaire (13 items, Likert scale 1-5), observation of method implementation, and documentation. Instrument validity was tested using Pearson product-moment correlation (r calculated > r table), while reliability was tested using Cronbach's alpha (α > 0.70). Data analysis utilized an independent-samples t-test in SPSS 26.0, preceded by normality tests (Kolmogorov-Smirnov and Shapiro-Wilk) and a homogeneity test (Levene's test). Research findings revealed a significant difference in students' learning motivation between experimental and control classes. The experimental class posttest mean score (48.63) was higher than the control class (43.47), with t-calculated = 3.653 > t-table = 2.00 and significance value 0.001 < 0.05. The motivation gain score for the experimental class (16.20) was higher than that of the control class (12.40). These findings indicate that the targhib wa tarhib method effectively enhances students' learning motivation in Islamic Religious Education through a combination of positive reinforcement and educational consequences, thus it can be implemented as an alternative learning strategy to increase student enthusiasm and active participation.